THE GROSS ALFA AND GROSS BETA ACTIVITIES OF HOLOCENE MARINE SEDIMENTS AND THE RELATIONSHIP OF THESE ACTIVITIES WITH RADIONUCLIDES IN THE WESTERN MARMARA SEA, TURKEY - Yumun, Z. U.; Yentur, M. M.; Asliyuksek, H.; Kam, E. (ALOKI Applied Ecological Research and Forensic Inst Ltd, 2022)
The aim of this study is to analyze the gross alpha and gross beta activities of Holocene marine sediments and to determine the relationship of these activities with radionuclides in the west of Marmara Sea (Turkey). Background and anthropogenic ionizing radiations are the main sources of environmental radioactivity human beings are exposed to. Background radiation occurs as a result of cosmogenic and terrestrial radiation, while anthropogenic refers to man-made radiation. In this context, gross alpha and beta activity of sea sediment samples collected at 29 different stations in the research region were analyzed using the low-background counter (Berthold, LB 770, 10- channel alpha-beta low-level counter). Also, the relation between abundance of radioactive isotopes and alpha and beta activity were discussed in this paper. As a result, the average gross alpha and beta activities were determined as 223.18 +/- 14.9 Bq kg(-1) and 572.00 +/- 23.9 Bq kg(-1), respectively. The results obtained can be used as a data base for Holocene marine sediments.
Keywords: radionuclide; radioactivity; radioactivity pollution; Chernobyl accident K-40; Sr-90; Cs-137; Marmara Sea; HEAVY-METAL POLLUTION; NATURAL RADIONUCLIDES; AEGEAN SEA; FORAMINIFERA; IZMIR; WATER; GULF; Environmental Sciences & Ecology